2015
DOI: 10.1093/gji/ggv294
|View full text |Cite
|
Sign up to set email alerts
|

Ground motions induced by a producing hydrocarbon reservoir that is overlain by a viscoelastic rocksalt layer: a numerical model

Abstract: S U M M A R YHydrocarbon reservoir pressure depletion leads to stress changes inside the reservoir and ground deformation which is registered at the surface as subsidence. As reservoirs are often overlain by layers of rocksalt (or other evaporites), which are materials that flow so as to relax stresses inside them, there is the potential for time-varying surface subsidence. This work focuses on understanding the macroscopic mechanisms that lead to rocksalt flow-induced ground displacements. A Finite Element Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Shallow surface deformation should be manifest as short‐wavelength features superimposed on the regional signal (Bourne & Oates, ). Possible near‐surface deformation (e.g., soil mobility and salt flow effects; Marketos et al, ) are expected to be small and are neglected in this work. In addition, a region to the south of the reservoir that comprises the Veendam dissolution salt mine is removed from the data set to minimize the effect from this unrelated shallow surface deformation.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Shallow surface deformation should be manifest as short‐wavelength features superimposed on the regional signal (Bourne & Oates, ). Possible near‐surface deformation (e.g., soil mobility and salt flow effects; Marketos et al, ) are expected to be small and are neglected in this work. In addition, a region to the south of the reservoir that comprises the Veendam dissolution salt mine is removed from the data set to minimize the effect from this unrelated shallow surface deformation.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…This work focuses on one such mechanism (creep of the rock salt caprock material) highlighting the effects it can have on observed subsidence patterns above a producing gas reservoir. Our previous work [ Marketos et al , , ] has shown that creep of rock salt caprock, in response to shear stresses induced in it by the production process, can, in its own right, produce significant time‐dependent ground deformations that will alter the subsidence patterns and their evolution compared with fully elastic analyses. We showed that, if salt creeps according to a linear viscous flow law, the subsidence bowl initially deepens and narrows and then, over large timescales, becomes shallower and wider.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that, if salt creeps according to a linear viscous flow law, the subsidence bowl initially deepens and narrows and then, over large timescales, becomes shallower and wider. In that work, we focused on geomechanical models that were the simplest possible, investigating the system response to a step decrease in pore pressure as applied to the simplest possible reservoir shapes, i.e., shapes approaching point sources (a flat cylinder in 2‐D plane strain conditions and a sphere in 2‐D axisymmetric conditions—[ Marketos et al , , ], respectively). We neglected, among other factors, the effect of depletion rate (i.e., reservoir pressure decrease rate) on subsidence evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the model is relatively computationally inexpensive compared with the more accurate numerical solutions produced by Finite Element Methods (FEM), commonly adopted for simulating surface subsidence and reservoir compaction (e.g., Minkoff et al, 2003;Marketos et al, 2015). The effort required to adequately characterize complex constitutive models (e.g., material rheology, reservoir geometry, and inhomogeneity) and develop stable mesh attributes mean the repetitive calculations of complex simulations typical of FEM can make these approaches impractical.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%